THE EFFECT OF STIMULANTS ON THE NUMBER OF BUSHES AND PRESERVATION LEVEL OF THE NAFIS VARIETY OF SOYBEAN - Usmonova Shokhista Usman kizi; Atabaeva Halima Nazarovna; Khayrullaev Sardor Shamsiddin ugli3 (Journals Park Publishing, 2023)
This article presents information on the influence of methods of applying stimulants on the number of stems of soybean "Nafis". According to him, the application of stimulants to plants increases their resistance to abiotic factors. All the stimulators in the experiment showed their effect for the preservation of the plant, and the foliar feeding variant of the fulvogummat stimulator showed a better result than the other stimulators.
Keywords: agrotechnics, growth, development, stimulants, basis of fertilizers, plant number and level of preservation.